1983
DOI: 10.1007/bf01658080
|View full text |Cite
|
Sign up to set email alerts
|

Limb ischemia caused by small artery disease

Abstract: The pathophysiology and clinical manifestations of limb ischemia due to small artery diseases are reviewed, based on records from over 400 patients who were examined since 1971. Details of prospective clinical, laboratory, and angiographic evaluation and long‐term follow‐up are presented. The predilection of small artery diseases for the upper extremity remains unexplained. Preliminary results with the use of nifedipine for chronic treatment of vasospastic symptoms are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…6 In contrast, another series identified small artery spastic or occlusive disease limited to the hands and fingers as the cause of ischemia in more than 95% of patients. 7 Our study revealed that the 5-year survival rate from the index surgery of the surgical group was half that of the nonsurgical group (35% vs 70%), thus supporting our hypothesis. Koch et al 8 concluded that the prevention of limb ischemia (and coronary artery disease) in ESRD patients on dialysis was of utmost importance to improve survival.…”
Section: Discussionsupporting
confidence: 89%
“…6 In contrast, another series identified small artery spastic or occlusive disease limited to the hands and fingers as the cause of ischemia in more than 95% of patients. 7 Our study revealed that the 5-year survival rate from the index surgery of the surgical group was half that of the nonsurgical group (35% vs 70%), thus supporting our hypothesis. Koch et al 8 concluded that the prevention of limb ischemia (and coronary artery disease) in ESRD patients on dialysis was of utmost importance to improve survival.…”
Section: Discussionsupporting
confidence: 89%
“…PAD is a “silent” disease that manifests in only 5% of the patients with ischemic upper extremities. 1 , 2 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…PAD is a "silent" disease that manifests in only 5% of the patients with ischemic upper extremities. 1,2,11 The prevalence of PAD varies according to the ethnicity and geographic location, with a higher prevalence reported in Australian, African-American, and Hispanic populations. 12,13 Between 2000 and 2010, the global prevalence of PAD increased by 5% (approximately 200 million patients).…”
Section: Introductionmentioning
confidence: 99%